2013
DOI: 10.1186/1476-511x-12-52
|View full text |Cite
|
Sign up to set email alerts
|

Selective deposition of dietary α-Lipoic acid in mitochondrial fraction and its synergistic effect with α-Tocoperhol acetate on broiler meat oxidative stability

Abstract: The use of bioactive antioxidants in feed of broiler to mitigate reactive oxygen species (ROS) in biological systems is one of promising nutritional strategies. The aim of present study was to alleviate ROS production in mitochondrial fraction (MF) of meat by supplemented dietary antioxidant in feed of broiler. For this purpose, mitochondria specific antioxidant: α-lipoic acid (25 mg, 75 mg and 150 mg) with or without combination of α-tocopherol acetate (200 mg) used in normal and palm olein oxidized oil (4%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
(46 reference statements)
5
4
0
Order By: Relevance
“…Nuggets from the group that was fed only basal diet contained much lower quantities of both ALA (6.14 mg/g) and AT (7.63 mg/g). The results are in agreement with the findings of Yasin et al [36] and Parveen et al [37] who speculated that the chickens whose diet was supplemented with higher quantities of ALA (150 mg/Kg) showed higher content of ALA and AT deposited in the raw meat. Khan et al [12] also supported the idea of the synergism between ALA and AT because ALA regenerates some other antioxidants as mentioned above.
Fig.
…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Nuggets from the group that was fed only basal diet contained much lower quantities of both ALA (6.14 mg/g) and AT (7.63 mg/g). The results are in agreement with the findings of Yasin et al [36] and Parveen et al [37] who speculated that the chickens whose diet was supplemented with higher quantities of ALA (150 mg/Kg) showed higher content of ALA and AT deposited in the raw meat. Khan et al [12] also supported the idea of the synergism between ALA and AT because ALA regenerates some other antioxidants as mentioned above.
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…FRAP (624.84 μmol/Fe +2 /g meat) and TPC (87.62 mg GAE/100 g meat) were higher at 45th day of storage in nuggets from the group fed with WGO + ALA, whereas the values were lower in control group (559.67 μmol/Fe +2 /g meat and 87.62 mg GAE/100 g meat). Different studies proved that there was positive correlation between the antioxidant activities and total phenolic contents in raw and cooked chicken meat [ 11 , 35 37 ]. The results showed that the antioxidant potential was higher in the meat from the group fed with both natural antioxidant (WGO) and ALA.…”
Section: Resultsmentioning
confidence: 99%
“…Alpha-tocopherol acetate content was increased as the supplementation of α-lipoic increased with constant level of α-tocopherol and it ranged from 79.09 to 206.43 mg/g in breast meat on dry basis. The results of this study are in agreement with [ 5 , 32 ] who also stated that the alpha-lipoic acid concentration increase the alpha-tocopherol deposition.…”
Section: Resultssupporting
confidence: 92%
“…() and Parveen et al . () have also depicted that broilers receiving α‐tocopherol in feed gain higher body weight and better feed conversion efficiency.…”
Section: Resultsmentioning
confidence: 92%
“…In another study, Parveen et al . () reported that ABTS + reducing activity is higher in the treatment where higher dose of antioxidants supplemented in the feed of broiler birds.…”
Section: Resultsmentioning
confidence: 96%